(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Stability studies are essential for assessing the quality, safety, and efficacy of pharmaceutical products, ensuring they maintain their properties over time. This study aimed to assess the stability of metronidazole tablets stored in a desiccator with charged silica gel following the International council for harmonization of Technical Requirements for Pharmaceuticals for Human Use guidelines. Metronidazole tablets were formulated from metronidazole co-agglomerates using different excipients by direct compression method and stored for 6 and 12 months at 25±2°C/60±5% relative humidity. Quality parameters such as weight variation, diameter, thickness, hardness, friability, content uniformity, and dissolution rate were evaluated at intervals using the United States Pharmacopeia – National Formulary and British Pharmacopeia specifications. The tablets maintained uniformity in weight, diameter, thickness and content over 12 months, meeting pharmacopeial standards. They exhibited high crushing strength, low friability, and consistent disintegration times (<5 min), across formulations and storage durations with no significant changes after storage, indicating stable performance. The sustained high crushing strength, friability ratio (CSFR) and crushing strength, friability, disintegration time (CSFR/Dt) ratios suggested high tablet strength and quality. In-vitro dissolution studies showed release rates of 87.31 – 100.81 %, with a significant decrease at 6 months within pharmacopeial standards but no change at 12 months. Content uniformity was maintained throughout storage. Metronidazole tablets formulated from crystallo co-agglomerates demonstrated good stability and mechanical strength over 12 months of storage. Storage in air-tight containers with desiccants at controlled room temperature (25±2°C) or below their relative humidities is recommended for maintaining tablet quality